Three-Pass Protocol Concept in Hill Cipher Encryption Technique - Andysah Putera Utama Siahaan (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2016)
Encryption is imperative in the world of computers. Delivery of data requires a technique that the data is free from attack. Hill Cipher is the popular cryptography method. There are so many techniques that have been made to dismantle the message. Hill Cipher uses the symmetric key model. This key must be distributed to the recipients so that they can restore the ciphertext into plaintext. To avoid the key interception, the Three-Pass Protocol can be implemented to this situation. It avoids the key delivery. By using this technique, either the sender or the recipient does encryption and decryption by their keys respectively without sharing them with each other. It is impossible to the attacker to get the key since the both participants keep the keys safely. Hence, the information transmission is more secure than not using this concept.